2020
DOI: 10.3389/fphar.2020.00180
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Endothelin System in Colorectal Cancer Liver Metastasis: Influence of Epigenetic Mechanisms?

Abstract: Targeting of endothelin system genes is a promising strategy in cancer therapy. The modulation of these genes was explored in a model of colorectal cancer (CRC) liver metastasis and in a panel of CRC tumor cell lines that were exposed to the demethylating agent decitabine. The CC531 rat model mimicking CRC liver metastasis was used for tumor cell re-isolation and analysis of the endothelin system genes and DNA methyltransferases (DNMTs) by microarray. To mimic the effects caused by methylation changes, a panel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…In addition, Fu et al (42) reported that miR-124-3p suppressed cell proliferation and invasion by the direct regulation of EDNRB in bladder cancer. By contrast, EDNRB expression has been shown to be downregulated by aberrant hypermethylation in the promoter site in several tumors, including hepatocellular carcinoma, gastric cancer and CRC (43)(44)(45). A reduced EDNRB expression by hypermethylation has been found to be associated with gastric cancer invasion and to be associated with pathological stage in prostate cancer (46).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Fu et al (42) reported that miR-124-3p suppressed cell proliferation and invasion by the direct regulation of EDNRB in bladder cancer. By contrast, EDNRB expression has been shown to be downregulated by aberrant hypermethylation in the promoter site in several tumors, including hepatocellular carcinoma, gastric cancer and CRC (43)(44)(45). A reduced EDNRB expression by hypermethylation has been found to be associated with gastric cancer invasion and to be associated with pathological stage in prostate cancer (46).…”
Section: Discussionmentioning
confidence: 99%
“…A new study points out the mechanism exerted by methylation on endothelin system genes expression can be compromised in CRLM. 317 Notably, CSCs are critical for the formation and maintenance of liver metastasis. Together, our data highlights distinct CSC dependencies for primary versus metastatic tumor growth and suggest that targeting CSCs may be one direction of treatment for CRLM.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%
“…When metastatic cell lines were exposed to Decitabine (DAC, which inhibits DNA methyltransferases), the expression of endothelin system genes did not increase, indicating that these gene expression changes were not caused by DNA methylation. This suggests that the regulatory function of epigenetic alterations may be gradually lost in the late stage of metastasis [ 67 ]. The microenvironment-induced epigenetic mutation is an essential mechanism for metastatic tumor cells to grow in their new niche.…”
Section: The Underlying Molecular Mechanisms and Contributing Factors...mentioning
confidence: 99%